Effect of 2% Chlorhexidine on Shear Bond Strength of Composite Resins to Dentin - Maryam Zare Jahromi; Parvin Mirzakouchaki Boroujeni; Mohammad Reza Saei; Negin Riyazifar; Parisa Ranjbarian; Arian Moshreffar (Islamic Dental Association of Iran, 2015)
Background and Aim: Intracanal medicaments can affect the bond strength of composite to dentin. The aim of this study was to evaluate the effect of 2% chlorhexidine (CHX) gel as an intracanal medicament on shear bond strength of three different composite resins to dentin. Materials and Methods: In this in-vitro study, 60 intact extracted human premolars were utilized. Each tooth was sectioned vertically and dentin of the buccal surface was exposed. Then, specimens were divided into six groups of 10 teeth. In groups 1-3, dentin was exposed to CHX and in groups 4-6, dentin was exposed to saline. All prepared surfaces were rinsed with distilled water and dentin bonding agent specific for each composite was applied on the dentin surfaces. Z100, Z350 and P90 composites were applied to the treated surfaces and cured. The shear bond strength was recorded in Newtons and converted to MPa. Data were analyzed using the Kruskal-Wallis and Dunn tests. Results: The lowest mean shear bond strength was reported for normal saline and Z100 composite group (18.47 MPa) and the highest for CHX and Z350 group (42.26 MPa). No statistically significant difference in bond strength values was found between normal saline and CHX groups (P>0.05). There was a significant difference in bond strength values of different composite resins in normal saline (P<0.05) and also in CHX groups (P<0.05). Conclusion: Application of 2% chlorhexidine gel slightly but not significantly increases the mean shear bond strength of composite to dentin. The type of composite influences the shear bond strength to dentin.